Sinergitas Pemerintah Kota Salatiga dan Stakeholder Dalam Menjaga Kerukunan Umat Beragama - Ryansani - Oktavian; Turtiantoro - - (Journal of Politic and Government Studies, 2020)
Pluralism in the city of Salatiga can be a crucial issue that always threatens unity and integrity, because every small group now has the opportunity to claim the right to live properly and to be treated equally without discrimination. It is in the interest of all individuals to provide a justification for the ideas they want and force them on other groups in an anarchic way. With the diversity of religions, ethnicities, and races in the City of Salatiga, of course it is a difficult problem to maintain tolerance and harmony but the City of Salatiga can show its ability to maintain the conducive attitude of tolerance and harmony between religious communities because of respect and appreciation on the differences between one another, it has become a habit for the people of Salatiga City and has been embedded since a long time ago as evidenced by the City of Salatiga which had been awarded as the most Tolerant city 3 times. The success of the City of Salatiga in maintaining harmony and tolerance of religious communities until now cannot be separated from unity between the Government and the Salatiga City community.The research method in this study is descriptive research with a qualitative approach. The writer obtains the research data from interviews, observations and reinforced with documentation in accordance with the focus of the problem regarding the Synergy of the Salatiga City Government and Stakeholders in Maintaining Inter-Religious Harmony, the research location is in the City of Salatiga.Based on the results of the research and discussion that has been done, it can be concluded that; First, the Government's efforts with Stakeholders in maintaining conducive harmony between religious communities in the City of Salatiga are carried out through programs and activities that involve and bring together interfaith, ethnicity, ethnicity and race which are held regularly. Second, many parties are involved and take an active role in maintaining the conducive and tolerant attitude in the city of Salatiga apart from the government itself from civil society, mass organizations, religious knots in the City of Salatiga to support each other and synergize in carrying out and maintaining a successful tolerance attitude. The harmony that exists in the City of Salatiga is the main key to maintaining harmony in the City of Salatiga which is to establish good coordination and synergy between the government and stakeholders. Third, regarding the problems, obstacles and challenges faced by the Salatiga City Government in maintaining an attitude of tolerance and harmony, namely in the form of vigilance against prohibited organizations that cause intolerance and problems related to the establishment of places of worship.